New bis(benzimidazol-2-ylidene)pyridine-nickel complexes as homogeneous catalysts - Travers, Guy (Curtin University, 2015)
New nickel-based catalysts for carbon-carbon bond formation reactions were synthesized and tested. The catalysts were found to be effective, but not strongly influenced by changes in the catalyst structure. During the course of this work, an organic precursor was found to catalyse the decomposition of dimethylsulfoxide. A product of the decomposition was isolated in good yield and identified. This product was found to be a useful reagent for epoxidation reactions.